Perancangan Sistem E-Commerce Menggunakan Model Rapid Application Development Pada Pengurus Cabang Judo Karawang - Atang Saepudin; Riska Aryanti; Eka Fitriani; Dian Ardiansyah (Paradigma, 2021)
The development of information technology which is increasingly advanced and dynamic and the increasing competition in the global market has made all competition, both labor and business sectors, tighter. Of course this affects all types of businesses and business actors must start thinking about new breakthroughs so that their business can survive and be able to compete with other business competitors. The lack of breakthrough in marketing is experienced by the Judo Karawang Branch Management, where marketing is the spearhead of a business. So, if the marketing strategy is blunt, it will have an impact on the process of business activities. In order for these businesses to survive, the use of information technology is of course the main choice in business development, especially in terms of promotion and sales of services so that they can compete with other businesses. To increase competitiveness and to obtain other business opportunities, this can be done by taking advantage of developments in Information and Communication Technology (ICT). The system development method used in this study is the Rapid Application Development model. This model is used because it is considered a development method that has a short and fast development time. Referring to previous research, the researcher chose this RAD model because it was considered appropriate for the e-commerce system that the researcher built. E-commerce will make it easier for producers in marketing activities and also cut operating costs for trading and marketing activities so that it will increase sales volume and increase revenue. This increase in income will eventually expand the business.